Sam-animation software for simulating articulated motion - Klein, Charles A., author; Maciejewski, Anthony A., author; Pergamon Press Ltd., publisher (Colorado State University. Libraries, 1985)
A collection of software used for interactive specification, motion control and graphics simulation of articulated objects of arbitrary complexity is described. While used primarily for simulating and evaluating robotic manipulators, it has also been applied to the animation of biological models. One of the key issues discussed involves a flexible and intuitive approach to the motion specification for that large class of objects which possess redundant degrees of freedom.
Keywords: manipulator design; coordinate systems; robotic simulations; motion control; Jacobian matrices